ANNULMENT OF A TRADEMARK FOR BAD FAITH - Roxana CATEA (Challenges of the Knowledge Society)
When entering any new potential market or trying to establish a name for oneself on a designated market, one of the first steps taken by any economic operator, apart from actually rendering the service or conceiving the product which is envisaged to be sold, is establishing the brand designated to identify it. Unfortunately, in several scenarios, the band name is already taken, either by an aggressive competitor or by a „well-intended” contractual partner. Since in such cases, the name intended to be used as a trademark has already been unlawfully secured, interested parties may request its annulment, provided that the bad faith of the applicant is duly sustained with arguments and proofs. The purpose of this article is to address the concept of „bad faith” from a practical perspective, considering the Romanian courts’ recent optics of this open concept, based on the European Court of Justice’s principles and guidelines. The objectives of this article are outlining the different approaches of Romanian intellectual property courts insofar as bad faith is concerned, and explaining how the concept has evolved, based on the subjective and the objective element within the court’s analysis. Also, the article aims to better characterize the court’s standpoint with respect to bad faith in commercial relationships.